INCREASING VISIBILITY AND LOCAL ECONOMY THROUGH DIGITAL MARKETING: A CASE STUDY OF THE PANGALENGAN VILLAGE TOURISM MARKET - Yuliafitri, Indri; Hakim, Ahmad Luqman (LPPM Univ. Ibn Khaldun Bogor, 2025)
This article details the implementation of a community service program at Pasar Wisata Desa Pangalengan, Bandung Regency, focusing on enhancing visibility through digital marketing. Despite its significant economic and tourism potential, the market faced substantial promotional challenges. The implemented solution involved the creation and management of Instagram and TikTok social media accounts, alongside the publication of creative and informative content. Methods employed included surveys, market research, material presentations, and interactive discussions. Initial results indicate a significant increase in reach and interaction on social media platforms, particularly through video content, contributing to enhanced appeal and local economic potential.